INDUSTRIAL TEMPERATURE MONITORING AND CONTROL SYSTEM THROUGH ETHERNET LAN (International Journal of Engineering and Computer Science, 2017)
This paper presents a PC based temperature monitoring and control system using virtual instrumentation, LabVIEW. Data acquisition is an important role in industry in order to ensure the quality of service. Temperature sensor measures the temperature and produce corresponding analog signal which is further processed by the microcontroller. The simulator acquires data from the microcontroller through Ethernet port. The data will be displayed on the LCD in microcontroller and PC monitor. Automation and control can be done with the help of control circuitry